If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6q + -2 = 3q Reorder the terms: -2 + 6q = 3q Solving -2 + 6q = 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. -2 + 6q + -3q = 3q + -3q Combine like terms: 6q + -3q = 3q -2 + 3q = 3q + -3q Combine like terms: 3q + -3q = 0 -2 + 3q = 0 Add '2' to each side of the equation. -2 + 2 + 3q = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3q = 0 + 2 3q = 0 + 2 Combine like terms: 0 + 2 = 2 3q = 2 Divide each side by '3'. q = 0.6666666667 Simplifying q = 0.6666666667
| (y-2)-(7y-9)= | | 9p-4p+6=7p-3p | | -0.454545455p=-8 | | -3(2x-4)-16=8x+3 | | 2x+8(7)=18 | | 2(0)+8(7)=18 | | 3x-5=3x-7 | | 6(2x+8)=4(3x-6) | | x(x+12)=108 | | 0.08x-0.01(50)=1.9 | | x+3(x+2)=46 | | 50x^2=2 | | x+12x=108 | | -38-2x=10-8x | | x+10x=24 | | 8.164=2(3.14)r | | (5x-1)4=x+6 | | 1fourthm=10 | | 8.164=2(3.14) | | 65-2x=10x+18 | | 2(x+5)+4x-19=2x+7-2(3x) | | (5x+3)(x+2)(x-4)=0 | | y^2=13y | | 4x^2=32x | | 5-2x+6+7x=15-3x+2 | | -9x-10=-82 | | 3(x+7)-20=5x+7 | | 3+5+6+6+7+8+12*2= | | 6+-3b=-9 | | 9-c=-13 | | 6(x)+3(y)=4.80 | | z-8=-7 |